In Vitro and in Vivo Functions of Thrombin-Treated Platelets - Reimers, Hans-Joachim; Kinlough-Rathbone, Raelene L.; Cazenave, Jean-Pierre; Senyi, Andrew F.; Hirsh, Jack; Packham, Marian A.; Mustard, J. Fraser (Thrombosis and Haemostasis, 1976)
Thrombin-induced platelet aggregation has been generally believed to be irreversible. However, thrombin-induced aggregation of washed platelets is reversible if fibrin formation is prevented or the fibrin which binds the platelets together is removed from the platelet aggregates. After treatment with high concentrations of thrombin (0.5 units/ml) single platelets can be recovered that have lost practically all of their releasable serotonin and adenine nucleotides. These platelets are able to aggregate upon addition of low concentrations of ADP in the presence of fibrinogen. They aggregate in response to the ionophore A23, 187 in the absence of added fibrinogen, whereas sodium arachidonate-induced aggregation requires added fibrinogen. Thrombin-treated platelets change their shape in response to collagen in the absence of fibrinogen, and will aggregate upon the addition of collagen providing fibrinogen is present. This response to collagen can be blocked with aspirin but not with a mixture of creatine phosphate/creatine phosphokinase. Upon a second exposure to thrombin, thrombin-pretreated platelets do not change their shape and do not undergo aggregation. Thrombin-pretreated platelets will not retract a thrombin-induced fibrin clot unless ADP, sodium arachidonate, the ionophore A23, 187 or collagen are added together with thrombin.The ability of thrombin-treated platelets to adhere to the exposed subendothelial surface of the rabbit aorta is reduced, compared with untreated control platelets. The thrombin-treated platelets shorten the bleeding time of thrombocytopenic rabbits. However, they are not as effective in shortening the bleeding time as normal control platelets. When injected into rabbits with a normal platelet count, the thrombin-treated platelets that circulate after infusion survive for the same length of time as untreated control platelets. These findings indicate that thrombin-induced platelet aggregation with extensive release of granule constituents is not irreversible and that thrombin treatment does not cause irreversible damage of all platelets that would lead to their immediate elimination from the circulation. Furthermore, these platelets can still be haemostatically effective. It is conceivable that platelets that have lost their amine storage granule contents during a release reaction in vivo, such as may occur in certain cases of intravascular coagulation and repeated episodes of thrombosis, may be found in the circulation of man.